2020
DOI: 10.1109/access.2020.2983330
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Commutative Encryption and Data Hiding Scheme for HEVC Video

Abstract: In this paper, an improved commutative encryption and data hiding scheme for bit rate preservation of High Efficiency Video Coding (HEVC) is proposed. To achieve commutative property, one set of syntax elements within the HEVC standard is utilized for data hiding, while another set is exploited for encryption. Specifically, the syntax elements including the sign of quantized transform coefficient (QTC), the sign of motion vector difference (MVD), and the magnitude of MVD are encrypted to perceptually distort t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Recently published papers proposed to embed a secret message using homomorphic encryption in multimedia files other than images, such as HEVC videos for example [28]. In our case, in future work, we are interested in applying the proposed method to 3D meshes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published papers proposed to embed a secret message using homomorphic encryption in multimedia files other than images, such as HEVC videos for example [28]. In our case, in future work, we are interested in applying the proposed method to 3D meshes.…”
Section: Discussionmentioning
confidence: 99%
“…Here, watermarking of residual DCT coefficients is based on Quantized Index Modulation (QIM) [11]. In [12], in order to achieve the commutative property, one set of syntax elements within the HEVC bitstream is utilized for data hiding, while another set is exploited for encryption. In [13] and [14], the JPEG-LS bitstream is jointly watermarked and encrypted using the AES algorithm in Cipher Block Chaining (CBC)-mode, making this scheme suitable for scenarios with high security requirements, like in medical imaging.…”
Section: Related Workmentioning
confidence: 99%
“…A summary of the most recent image and video ciphering techniques is provided in this section. In [32], the authors suggested an enhanced hybrid data hiding and ciphering approach for information protection of HEVC streams. The proposed hybrid approach exploits the syntax elements of the sign of motion vector difference (MVD), the sign of quantized transform coefficient (QTC), and the magnitude of MVD of the compressed HEVC streams for data hiding and ciphering processes.…”
Section: Review Of Related Workmentioning
confidence: 99%